BIOSORPTION OF HEXAVALENT CHROMIUM BY Spirogyra spp.: EQUILIBRIUM, KINETICS AND THERMODYNAMICS - A. Yaqub; M. S. Mughal; A. Adnan; W. A. Khan; K. M. Anjum (Journal of Animal and Plant Sciences, 2012)
Uptake of hexavalent chromium (Cr VI) using dead biomass of green algae, Spirogyra spp. to evaluate biosorption capacity with special emphasis on its mechanistic aspect was studied. Optimum biosorption of Cr (VI) was observed at pH 4.0 (265mg/g), biomass concentration of 1mg/g, and temperature 303K.Various adsorption isotherms were employed to analyze the experimental data of which Langmuir isotherm was found most suitable, showing monolayer adsorption. Pseudo-second order model was found suitable for the kinetic interpretation of the data. Various thermodynamic parameters were calculated and the biosorption was found to be spontaneous, endothermic and feasible under the given conditions. Analysis of FTIR spectra indicated the presence and role of electronegative functional groups on algal surface responsible for binding of Cr (VI) ions.
Keywords: Biosorption; Green algae; Heavy metals; Kinetic; Thermodynamic; FTIR